2004
DOI: 10.1097/01.asn.0000113321.49771.2d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin II Receptor Blockage on Osteopontin Expression and Calcium Oxalate Crystal Deposition in Rat Kidneys

Abstract: Abstract. Hyperoxaluria leads to calcium oxalate (CaOx) crystallization and development of tubulointerstitial lesions in the kidneys. Treatment of hyperoxaluric rats with angiotensin II (Ang II) type I receptor blocker (ARB) reduces lesion formation. Because Ang II mediates osteopontin (OPN) synthesis, which is involved in both macrophage recruitment and CaOx crystallization, it was hypothesized that ARB acts via OPN. Hyperoxaluria was induced in 10-wk-old male Sprague-Dawley rats, and they were treated with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 61 publications
(66 reference statements)
5
60
0
Order By: Relevance
“…Several studies have confirmed the inhibitory effect of ARBs by suppressing oxidative stress and tubule-interstitial injury through inhibition of osteopontin expression. 103 In this study, administration of telmisartan and cystone showed amelioration in the EG-induced urolithiasis in uninephrectomized hypertensive rats via modulation of ROS; however, it failed to produce any significant down-regulation in the KIM-1 and NGAL mRNA expression. In conclusion, L-arginine showed the nephro-protective and cardioprotective property against EGinduced urolithiasis in uninephrectomized hypertensive rats via modulation of KIM-1, NGAL, eNOs, and iNOs mRNA expression.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have confirmed the inhibitory effect of ARBs by suppressing oxidative stress and tubule-interstitial injury through inhibition of osteopontin expression. 103 In this study, administration of telmisartan and cystone showed amelioration in the EG-induced urolithiasis in uninephrectomized hypertensive rats via modulation of ROS; however, it failed to produce any significant down-regulation in the KIM-1 and NGAL mRNA expression. In conclusion, L-arginine showed the nephro-protective and cardioprotective property against EGinduced urolithiasis in uninephrectomized hypertensive rats via modulation of KIM-1, NGAL, eNOs, and iNOs mRNA expression.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, we have shown that CaOx crystal deposition in rat kidneys activates the renin-angiotensin system and increases renin expression in the kidneys and serum. 47 Recent studies have shown OPN to be a monocyte chemoattractant specifically for the renal interstitium and that up-regulation of OPN precedes the interstitial monocyte infiltration. 48,49 OPN knockout studies demonstrated a reduced influx of macrophages into obstructed kidneys of knockout mice compared to wild-type mice at days 4 and 7 but not at day 14.…”
Section: Animal Model Studiesmentioning
confidence: 99%
“…The SOD activity in the supernatant of kidney homogenate were measured spectrophotometrically [11] using a kit from the Nanjing Jiancheng Biochemistry (China, Cat:A001) according to the manufacturer's protocol. The concentration of angiotensin II was measured by radioimmunoassay method [22] using a kit from the North Biochemistry Institute (China). The total SOD activity and the total amount of Ang II were corrected by kidney weight.…”
Section: Kidney Tissue Preparationmentioning
confidence: 99%
“…Tissue culture studies have indicated involvement of the NADPH oxidase in Ox-induced ROS production and cell injury [10,21]. Furthermore, hyperoxaluria and crystal deposition has been found to activate the renal renin-angiotensin system (RAS) [22][23][24].…”
Section: Introductionmentioning
confidence: 99%